Impact of environmental practices on visitor loyalty in tourist destinations: A systematic review - Condori-Chura, Delia (2025)
The sustainability trend has motivated the inclusion of eco-friendly practices in tourist destinations and companies as a competitive factor by promoting environmental responsibility to attract environmentally conscious visitors. In this context, the study aimed to evaluate the impact on tourist loyalty in specific tourist destinations through a literature review. A systematic review approach was employed using the PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), reviewing works from the PubMed, Scopus, and Web of Science databases to gather existing literature on the subject. It was found that the implementation of sustainable strategies, such as reducing energy consumption, implementing efficient recycling systems, using eco-friendly cleaning products, responsible water management with the installation of water-saving devices, promoting local tourism, and green certifications, are particularly effective in hotel management, improving tourists’ perceptions of sustainability and increasing their loyalty to the destination. In conclusion, implementing sustainable strategies in tourist spaces significantly impacts the tourist experience, increasing their loyalty to the destination.